Between Mariners, Pirates and Priests: An Introduction to The World of Ship Graffiti In Medieval Mediterranean - Ioannis Nakas (Papers from the Institute of Archaeology, 2021)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Ship graffiti are one of the most common illustrations or vandalisms found on the walls of medieval and post-medieval monuments in Mediterranean countries. A multitude of vessels of various types and sizes have been carved or drawn by the people of the Middle Ages on monuments, such as the Parthenon and the cathedral of Majorca, and humble buildings, such as cisterns and baths. Who made these graffiti? And why? Their occurrence in places of worship (churches, mosques) indicates that they were tokens of suppliance and votives, but equally common is their appearance in secular buildings, often related with water (baths, fountains, etc.). Moreover, their quality ranges from simplistic ‘banana boats’ to highly accurate representations of ship hulls and their rigging. This paper will examine certain case studies of medieval Mediterranean graffiti and propose different scenarios for the nature of their engravers or painters and the circumstances which led to their creation. Its aim is to explore the complicated relationship between the creation of ship graffiti and the contemporary world.
Keywords: Mediterranean; Medieval; Ships; Graffiti